SOSIALISASI PERMAINAN TRADISIONAL KHAS MAKASSAR - Sufitriyono Sufitriyono; Muhammad Akbar Syafruddin; Ikadarny Ikadarny; Haeril Haeril (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to introduce traditional Makassar games to Kartika Makassar high school students. The traditional games introduced in this activity are ma'boi, ma'dende, massantok, marbles, asing, and ma'cukke. Meanwhile, the subjects in this activity were members of the OSIS SMA Kartika Makassar. Socialization is done by lecture and practice methods. From the results of this activity, it can be concluded that students are getting to know Makassar traditional games, students and teachers at SMK Kartika Makassar are getting wider regarding traditional Makassar games, students know about the history and how to play Makassar traditional games, and through traditional Makassar games they are able to stimulate children's motor development compared to online games.